2018
DOI: 10.1002/hep.29573
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 15a/16‐1 suppresses aryl hydrocarbon receptor–dependent interleukin‐22 secretion in CD4+ T cells and contributes to immune‐mediated organ injury

Abstract: Our results suggest that miR-15a/16-1 acts as a essential regulator of IL-22 and that the miR-15a/16-1-aryl hydrocarbon receptor-IL-22 regulatory axis plays a central role in tissue repair; modulation of miR-15a/16-1 might hold promise in developing new strategies to enhance IL-22-mediated tissue repair. (Hepatology 2018;67:1027-1040).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Along these lines, a second study from the same group investigating the impact of IL-23 in acute liver injury confirmed a regulatory role of AHR by fine-tuning pro-inflammatory IL-17 as well as protective IL-22 responses [36]. Furthermore, the repression of AHR-dependent IL-22 expression in CD4+ T cells by microRNA 15a/16-1 led to exacerbated liver inflammation following ConA challenge, confirming the key role of AHR in controlling inflammatory responses in acute liver injury induced by ConA [37]. Interestingly, in a recent study, AHR has also been implicated in induction and mobilization of highly immunosuppressive myeloid-derived suppressor cells (MDSCs) from the peritoneal cavity.…”
Section: Ahr In Liver Immune Homeostasismentioning
confidence: 68%
“…Along these lines, a second study from the same group investigating the impact of IL-23 in acute liver injury confirmed a regulatory role of AHR by fine-tuning pro-inflammatory IL-17 as well as protective IL-22 responses [36]. Furthermore, the repression of AHR-dependent IL-22 expression in CD4+ T cells by microRNA 15a/16-1 led to exacerbated liver inflammation following ConA challenge, confirming the key role of AHR in controlling inflammatory responses in acute liver injury induced by ConA [37]. Interestingly, in a recent study, AHR has also been implicated in induction and mobilization of highly immunosuppressive myeloid-derived suppressor cells (MDSCs) from the peritoneal cavity.…”
Section: Ahr In Liver Immune Homeostasismentioning
confidence: 68%
“…All animal studies were performed in accordance with protocols approved by the Animal Subjects Committee of Beijing Anzhen Hospital. Mice carrying floxed alleles of mir15a/mir16-1 (Mirc30tm1.1Rdf/J mice) 13,14 were gifted by Dr. Yiwei Chu (Fudan University). The mice carrying floxed alleles of mir15a/mir16-1 were backcrossed to a C57BL/6 background at least ten times.…”
Section: Studies In Mouse Modelmentioning
confidence: 99%
“…In this regard, a key study has shown that IL‐22 promotes the expansion of liver progenitor/stem cells in mice and in patients with hepatitis B in a STAT3‐dependent manner . Furthermore, IL‐22 protects hepatocytes from apoptosis in a miR‐15a/16‐1‐dependent manner in mice . In addition, a number of studies have shown convincingly that IL‐22 strengthens the intestinal barrier by targeting intestinal stem cells and epithelial cells and by inducing important intestinal defensins or lectins such as Reg3β .…”
Section: Discussionmentioning
confidence: 99%